2012
DOI: 10.1111/j.1440-169x.2012.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of palate epithelial mesenchymal transition by transforming growth factor β3 signaling

Abstract: TGFβ3 is essential for palate development, particularly during the late phase of palatogenesis when the disintegration of the palatal medial edge seam (MES) occurs resulting in mesenchymal confluence. The MES is composed of medial-edge epithelium (MEE) of opposite palatal shelves; its complete disintegration is essential for mediating correct craniofacial morphogenesis. This phenomenon is initiated by TGFβ3 upon adherence of opposing palatal shelves, and subsequently epithelial-mesenchymal transition (EMT) ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 63 publications
(142 reference statements)
1
57
0
Order By: Relevance
“…Consistent with biochemical studies [18], the function of TGF-␤3 in palate fusion is mediated by Smad2, since the overexpression of Smad2 in Tgf-ˇ3 mutant palate epithelial cells rescues the fusion defect [29]. Interestingly, studies with palatal epithelium cells suggested that TGF-␤3 induces cell cycle arrest and epithelial to mesenchymal trans-differentiation (EMT), which could be a mechanism underlying TGF-␤3 in mediating palate fusion [30,31]. In addition, a recent study revealed that TGF-␤3 may also promote MEE fusion by activating the p38 MAPK pathway [32].…”
Section: Introductionsupporting
confidence: 57%
“…Consistent with biochemical studies [18], the function of TGF-␤3 in palate fusion is mediated by Smad2, since the overexpression of Smad2 in Tgf-ˇ3 mutant palate epithelial cells rescues the fusion defect [29]. Interestingly, studies with palatal epithelium cells suggested that TGF-␤3 induces cell cycle arrest and epithelial to mesenchymal trans-differentiation (EMT), which could be a mechanism underlying TGF-␤3 in mediating palate fusion [30,31]. In addition, a recent study revealed that TGF-␤3 may also promote MEE fusion by activating the p38 MAPK pathway [32].…”
Section: Introductionsupporting
confidence: 57%
“…Quantitative real-time PCR also revealed that NDZ inhibited the transcription factors, Snail and Zeb in the MEE. TGF-b/SMAD promotes EMT via induction of transcriptional repressors of E-cadherin including Snail and Zeb (Dave et al, 2011, Jalali et al, 2012, Pirozzi et al, 2011, Shirakihara et al, 2007. These findings indicated that microtubule disruption in the MEE led to a failure to down-regulate E-cadherin transcription via inhibition of the transcriptional repressors secondary to blockage of signaling from the TGF-b/SMAD2 pathway.…”
Section: Discussionmentioning
confidence: 72%
“…Transcriptional repression of E-cadherin is a key molecular event in EMT (Peinado et al, 2004). Down regulation of E-cadherin by transcriptional repressors such as the zinc finger factor Snail (Snai1 and Snai2), two-handed zinc finger factor Zeb (Zeb1 and Zeb2) is an essential mechanism by which TGF-b elicits EMT (Dave et al, 2011, Jalali et al, 2012, Pirozzi et al, 2011, Shirakihara et al, 2007. The signaling pathway is well known to induce EMT in MEE during palatal fusion (Kaartinen et al, 1997, Sun et al, 1998.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 In addition to Smads, non-Smad signaling contributes to the stabilization and activation of Snail1 and ZEB2 during palatal EMT, and additionally, the small GTPase Rho and its downstream Rho kinase contribute to mesenchymal phenotypic changes in the palate, including actin cytoskeleton remodeling. 55,56 Some additional examples of EMT can be listed based on their sensitivity to different TGFb isoforms. Similar to the heart, pulmonary valve morphogenesis requires EndoMT, which is driven by TGFb2 and is antagonized by the pro-angiogenic factor VEGF-A.…”
Section: Introductionmentioning
confidence: 99%